2011
DOI: 10.1002/cne.22566
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture of the lateral ganglionic eminence and rostral extension of the lateral ventricle in the human fetal brain

Abstract: The fetal development of the anterior subventricular zone (SVZ) involves the transformation of radial glia into neural stem cells, in addition to the migration of neuroblasts from the SVZ towards different regions in the brain. In adult rodents this migration from the anterior SVZ is restricted to the olfactory bulb following a rostral migratory stream (RMS) formed by chains of migratory neuroblasts. Similar to rodents, an RMS has been suggested in the adult human brain, where the SVZ remains as an active prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 72 publications
3
75
1
Order By: Relevance
“…Remarkably, in mammals, this chain-migrating source of cells appears to follow the remnant left behind by a shrunken ventricle (Kam et al 2009;Guerrero-Cázares et al 2011). In this context, chain migration in some mammals might have emerged as a solution to provide the olfactory bulb with new cells, despite the lack of ventricular connection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Remarkably, in mammals, this chain-migrating source of cells appears to follow the remnant left behind by a shrunken ventricle (Kam et al 2009;Guerrero-Cázares et al 2011). In this context, chain migration in some mammals might have emerged as a solution to provide the olfactory bulb with new cells, despite the lack of ventricular connection.…”
Section: Discussionmentioning
confidence: 95%
“…The polyclonal anti-GFAP antibody has previously been used as a glial marker in the olfactory system and brain of S. canicula (Wasowicz et al 1999;Sueiro et al 2007;Quintana-Urzainqui et al 2012b) and the monoclonal anti-PCNA specifically labels proliferating cells in the brain and olfactory epithelium of this species Ferrando et al 2010;Quintana-Urzainqui et al 2012b). The DCX is a microtubule-associated protein related to neurogenesis, neuronal migration and synaptogenesis that has been largely used to identify migrating neuroblasts along the RMS (Alvarez-Buylla and GarciaVerdugo 2002;Brown et al 2003;Curtis et al 2007;Balthazart et al 2008;Brill 2008;Brill et al 2008;Mendoza-Torreblanca et al 2008;Guerrero-Cázares et al 2011;Ming and Song 2011;Hodge et al 2012;Plachez and Puche 2012).The mouse monoclonal anti-reelin antibody (clone 142; Millipore, Billerica, MA; catalog number MAB5366) was raised against amino acids 164-189 of the protein. According to the manufacturer, the antibody recognizes three bands of approximately 400 kDa (full-length protein), 300 kDa and 180 kDa (cleavage products).…”
Section: Control and Specificity Of The Antibodiesmentioning
confidence: 99%
“…This is not very surprising, as it is known from rodent studies that only a small percentage of migrating cells will integrate into the olfactory bulb [1]. [10], which postulates that the RMS appears to be a real stream, complete with chain migrating neurons in the developing brain. In the adult brain, the stream becomes a trickle (see Figure 1).…”
mentioning
confidence: 93%
“…Previous studies have provided evidence suggesting that neurogenesis occurs in the adult human hippocampus [17]. Two studies have also indicated the presence of a putative RMS in the fetal human brain [18,19]. However, evidence for the presence of SVZ neurogenesis and an RMS-like pathway in the adult human brain remains highly controversial [14,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%